Benin : Poverty Reduction Strategy Paper-2005 Progress Report. (IMF Staff Country Reports; Country Report, 2008)
This Poverty Reduction Strategy Paper (PRSP) was developed based on a long participatory process based on an institutional mechanism involving all socioeconomic development actors in the country. The annual review of the PRSP seeks to assess the results achieved in the implementation of the poverty reduction strategy by analyzing the evolution of the performance indicators retained and the level of execution of the matrix of measures retained in the PRSP. This study is based on the reports of IMF staff's PRSP and information collected from government projects, program budget, and framework.